Theory of Vibration Protection - Karnovsky, Igor A.; Lebed, Evgeniy; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This text is an advancement of the theory of vibration protection of mechanical systems with lumped and distributed parameters. The book offers various concepts and methods of solving vibration protection problems, discusses the advantages and disadvantages of different methods, and the fields of their effective applications. Fundamental approaches of vibration protection, which are considered in this book, are the passive, parametric and optimal active vibration protection. The passive vibration protection is based on vibration isolation, vibration damping and dynamic absorbers. Parametric vibration protection theory is based on the Shchipanov-Luzin invariance principle. Optimal active vibration protection theory is based on the Pontryagin principle and the Krein moment method. The book also contains special topics such as suppression of vibrations at the source of their occurrence and the harmful influence of vibrations on humans. Numerous examples, which illustrate the theoretical ideas of each chapter, are included. This book is intended for graduate students and engineers. It is assumed that a reader has working knowledge of theory of vibrations, differential equations, and complex analysis. About the Authors. Igor A Karnovsky, Ph.D., Dr. Sci., is a specialist in structural analysis, theory of vibration and optimal control of vibration. He has 40 years of experience in research, teaching and consulting in this field, and is the author of more than 70 published scientific papers, including two books in Structural Analysis (published with Springer in 2010-2012) and three handbooks in Structural Dynamics (published with McGraw Hill in 2001-2004). He also holds a number of vibration-control-related patents. Evgeniy Lebed, Ph.D., is a specialist in applied mathematics and engineering. He has 10 years of experience in research, teaching and consulting in this field. The main sphere of his research interests are qualitative theory of differential equations, integral transforms and frequency-domain analysis with application to image and signal processing. He is the author of 15 published scientific papers and a US patent (2015).
From the Contents: Mechanical Exposure and Vibration Protection Methods -- Part I Passive Vibration Protection -- Vibration Isolation of Systems with One Degree of Freedom -- Part II Active Vibration Protection -- Pontryagin's Maximal Principle -- Krein's Moment Method -- Part III Shock and Transient Vibration -- Transient Vibration -- Shock and Spectral Theory.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Machinery; Aerospace engineering; Astronautics; Multibody Systems and Mechanical Vibrations; Machinery and Machine Elements; Aerospace Technology and Astronautics